ERITEMA MULTIFORME PASCA-VARISELA (Media Dermato Venereologica Indonesiana, 2020)
Erythema multiforme (EM) is a rare cutaneous or mucocutaneous eruption, characterized by target lesion. EM is caused by hypersensitivity reaction to various infections and drugs, including varicella and acetaminophen. A 23-year-old woman had typical target lesions preceded by varicella 6 days before. Varicella’s blister dried-up after valacyclovir, acetaminophen, and multivitamin were given. On the fourth day of varicella, hives arose and on the sixth day, typical EM lesion arose. Complete blood count was within normal limit, except slight eosinophilia. Patient was diagnosed as EM minor caused by drug eruption with differential diagnosis EM minor caused by varicella and Degos disease. Improvement was found after therapy of methylprednisolone, desloratadine, and moisturizing lotion. EM occurred 6 days after patient had varicella and consumed drugs. Drug eruption was suspected as the culprit because varicella lesions had improved with valacyclovir and there were hives preceding the target lesions. Among the drugs used, acetaminophen was suspected as the cause. Serologic testing for varicella and patch test or oral provocation test for drug allergy must be considered to determine the definitive diagnosis.